Short Term Alterations of Hormone Profile Following Oocyte Pick-Up in Women with Polycystic Ovarian Syndrome to Assess the Effect of Multiple Needle Entries Into the Ovarian Cortex and Stroma - Enis Ozkaya; Cigdem Abide Yayla; Semra Kayatas Eser; Belgin Devranoglu; Ilhan Sanverdi; Tayfun Kutlu (Medical Network, 2018)
Objective: Some hormonal alterations after ovarian diathermy have been proposed in previous studies. Based on this data, we aimed to analyze some hormone profile changes following oocyte pick-up in women with polycystic ovarian syndrome. Study Designs: A total of 50 women with polycystic ovarian syndrome underwent ovarian stimulation for IVF cycle with an indication of anovulatory infertility. Some hormone profiles with the insulin resistance were assessed before and after oocyte pick-up to (early in the morning before starting stimulation and repeated 1 month later from oocyte pick-up day) assess whether high number of needle entries into the ovarian cortex and stroma result in similar effect with the diathermy. Results: Comparison of some variables revealed significantly decreased HOMA-IR and serum total testosterone concentrations after intervention. Correlation analyses showed significant correlations between number of needle entries, change in HOMA-IR, baseline total testosterone level and change in AMH level. Conclusion: Our data showed significant metabolic and hormonal alterations following oocyte pick up consistent with the effect of ovarian diathermy in women with polycystic ovarian syndrome.